Correlation of European and U.S. Technology and Financial Stocks during COVID-19 Pandemic (International Journal of Applied Research in Management and Economics, 2023)
In 2022 stock markets around the world lost some of their value, led by high-growth sectors, sectors that tend to show a significantly higher growth rate than the average market. At the same time the financial sector shows a potentially higher interest rate sensitivity. The prevailing academic opinion is that central bank monetary policy during the COVID-19 pandemic is one key factor for the stock market development globally. This paper discusses the assumption of a significant technology and financial sector correlation for Europe and the United States from 2020 to 2022 based on market capitalization. The objective is fulfilled with a Pearson correlation for representative parts of STOXX Europe 600 and S&P 500. The results confirm significant correlation for the selected sectors and stocks for both regions, indicating potentially general sensitivity for the entire investigation period. Based on this, further research on sectors and potential alternative independent variables is recommended.